Hardness and wear behavior of CoO doped Fe-Al2O3 metal matrix composite (MMC) synthesized via powder metallurgy (P/M) technique - Gupta P.; Kumar D.; Parkash O.; Jha A.K. (My University, 2025)
In the present paper results of investigations on addition of cobalt oxide in the Fe-Al2O3 Metal Matrix Composite (MMC) synthesized via Powder Metallurgy (P/M) technique on phase, microstructure and mechanical characteristics are reported. X-Ray Diffraction, Scanning Electron Microscopy, density, hardness and wear measurement were used for characterization. XRD and SEM reveal that addition of cobalt oxide addition retards the formation of iron aluminate phase. Mechanical properties investigated include hardness and wear respectively. The measurement of wear of the specimens was done at a constant sliding velocity of 4 m/sec and under a load of 0.5, 1.0, 1.5 and 2.0 Kg. A correlation behavior was set up between the hardness and wear behavior of the composite specimens. It was found that hardness of the specimens was almost same in comparison to undoped Fe-Al2O3 MMC specimens. However, the ductility was improved and overall mechanical behavior of specimens was significantly improved. © (2012) Trans Tech Publications, Switzerland.